Self-Regulated Learning For Solving Mathematical Problems: A Systematic Literature Review - Noor, Naili Lumaati; Stevanus Budi Waluya; Sri Adi Widodo (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Yogyakarta, 2025)
As a mindset, mathematical problem-solving skills cannot be taught instantly but rather develop gradually. Meanwhile, self-regulation serves as a foundation in the learning process, encouraging increased student motivation and helping them reflect on their learning experiences. This study aims to provide a comprehensive overview of self-regulation learning for solving mathematical problems, including the role, process, and steps to improve self-regulation in solving mathematical problems. This Systematic Literature Review uses the PRISMA protocol as its implementation guide. The results show that the trend of self-regulation research in solving mathematical problems is dominated by descriptive qualitative and experimental approaches, with subjects varying from elementary school students to college students and teachers. Self-regulation has an important role in solving mathematical problems. The process of self-regulation in solving math problems involves a series of stages that help students manage their thoughts, emotions, and actions effectively. Some strategic approaches to improve mathematical problem solving through self-regulation are through the selection of appropriate learning methods, as well as monitoring learning progress and good emotional management by students. The implication of the research is to help educators understand the specific needs of students, so that self-regulation strategies can be tailored to the diverse abilities of students.